PROTEIN 24 HIV DAN LIMFOSIT T-CD4+ DI INFEKSI HIV TAHAP I (HIV p24 Protein and CD4+ T-lymphocyte in Stage I HIV infection) - I Made Sila Darmana; Endang Retnowati; Erwin Astha Triyono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Measuring HIV p24 protein is a test which is more practical than determination of CD4+ T-lymphocyte counts and viral load, asit does not require a very sophisticated instrument and requires a lower cost. Independent predictive value of p24 to the decline ofCD4+ T-lymphocytes, clinical progression and survival in HIV-infected patients have been reported. In this study, HIV-infected patientswere found to have HIV p24 protein levels inversely proportional to CD4+ T-lymphocyte counts by using Spearman test (R2=0.225;p=0.0331). Studies on the correlation between HIV p24 protein levels and CD4+ T-lymphocyte counts in stage I HIV infection have notyet been reported. The aim of this study was to prove the correlation between HIV p24 protein levels and CD4+ T-lymphocytes in stageI HIV infection. Research issue was whether a correlation between HIV p24 protein levels and CD4+ T-lymphocyte counts in stage I HIVinfection existed ? The hypothesis was that a correlation between HIV p24 protein levels and CD4+ T-lymphocyte counts in stage I HIVinfection existed. The study design was cross sectional observational. Subjects consisted of 30 stage I HIV-infected patients treated at theInfectious Disease Intermediate Care Unit, Dr. Soetomo Hospital and VCT Clinic of the Dr. Ramelan Naval Hospital, Surabaya from Mayto July 2014. Stage I HIV infection is an asymptomatic HIV infection or with persistent generalized lymphadenopathy and the patientis able to perform normal activities. Levels of p24 were measured by ELISA method and CD4+ T-lymphocyte counts using flowcytometry(BD FACSCaliburTM). The results were statistically analyzed using Pearson’s correlation test. HIV p24 protein levels in stage I of HIVinfection ranged from 1.8 to 10.8 pg/mL, mean of 5.14 pg/mL and a standard deviation of 2.08 pg/mL. CD4+ T-lymphocyte countsdecreased with a range of 49-559 cells /uL for absolute values and 4.42–26.02% for percentage values Correlations between blood p24levels and CD4+ T-lymphocyte counts either absolute (r=–0.392, p=0.032) or percentage (r=–0.363, p=0.049) were found. In stageI HIV-infected patients, a negative correlation was found between p24 levels and CD4+ T-lymphocyte counts, in both CD4+T-lymphocytecounts as absolute and as well as percentage values. This negative correlation showed that the p24 HIV levels were inversely proportionalto the CD4+ T-lymphocyte counts. HIV p24 protein levels have a possibility to be used predicting CD4+ T-lymphocyte counts.